2020
DOI: 10.1128/aac.01810-19
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Multidrug-Resistance Plasmid Carrying a Novel Macrolide-Clindamycin Resistance Gene, erm (50), in Cutibacterium acnes

Abstract: Antimicrobial-resistant Cutibacterium acnes strains have emerged and disseminated throughout the world. The 23S rRNA mutation and erm(X) gene are known as the major resistance determinants of macrolides and clindamycin in C. acnes. We isolated eight high-level macrolide-clindamycin-resistant C. acnes strains with no known resistance determinants, such as 23S rRNA mutation and erm(X), from different acne patients in 2008 between 2013 and 2015. The aim of this study was to identify the novel mechanisms of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…In addition, erm(X), encoding a RNA methylase that mediates resistance to clindamycin, has been identified on a mobile genetic element (Ross et al, 2002). Interestingly, a novel mobile genetic element of C. acnes was recently identified, conferring resistance to macrolides, clindamycin, and tetracyclines: the plasmid pTZC1 carries a novel macrolide-clindamycin resistance gene, erm(50), as well as a tetracycline resistance gene, tet(W) (Aoki et al, 2020). Resistant strains of C. acnes often belong to the acneassociated types, i.e., phylotypes IA 1 (SLST types A and C) and IA 2 (SLST type F) (Lomholt and Kilian, 2014;Nakase et al, 2017;Sheffer-Levi et al, 2020).…”
Section: Antimicrobial Resistance Of C Acnesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, erm(X), encoding a RNA methylase that mediates resistance to clindamycin, has been identified on a mobile genetic element (Ross et al, 2002). Interestingly, a novel mobile genetic element of C. acnes was recently identified, conferring resistance to macrolides, clindamycin, and tetracyclines: the plasmid pTZC1 carries a novel macrolide-clindamycin resistance gene, erm(50), as well as a tetracycline resistance gene, tet(W) (Aoki et al, 2020). Resistant strains of C. acnes often belong to the acneassociated types, i.e., phylotypes IA 1 (SLST types A and C) and IA 2 (SLST type F) (Lomholt and Kilian, 2014;Nakase et al, 2017;Sheffer-Levi et al, 2020).…”
Section: Antimicrobial Resistance Of C Acnesmentioning
confidence: 99%
“…This review will often refer to the main six phylotypes (and the 10 SLST types) and their distinct associations with health and disease. Apart from core genome differences, the accessory genome of C. acnes is relatively small but comprises elements such as a linear plasmid (designated p15.1.R1 or pIMPLE-HL096PA1, encoding a conjugation apparatus and a tight adherence pili locus) and a circular plasmid (designated pTZC1, encoding genes conferring resistance to macrolides, clindamycin and tetracycline) (Tomida et al, 2013;Davidsson et al, 2017;Aoki et al, 2020). In addition, around 60 other regions that are not part of the core genome can be identified in the pan-genome of C. acnes; these non-core genes are often, but not exclusively, phylotype-specific, and code for a variety of functions such as different transport systems, bacteriocin synthesis, resistance to heavy metals and antibiotics, restriction modification systems, CRISPR/cas systems, (cryptic) prophages, transposases, carbohydrate and amino acid processing enzymes, and many so far unknown functions (Brüggemann et al, 2012;Tomida et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis of the plasmids using the tool BRIG ( Figure 2 ) showed a deletion of approximately 10 kb in the plasmid of the C1 strain ZH8; this deletion was not detected before in any known plasmid sequence. Another plasmid, designated pTZC1, conferring resistance to macrolides, clindamycin, and tetracyclines, which has been found in C. acnes strains isolated in Japan, could not be identified in any of the 16 strains sequenced here [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the Erm family, a total of 44 sequences were aligned, where 41 of them could be retrieved from CARD (comprehensive antibiotic resistance database; [ 22 ]) and ErmI [ 23 , 24 ], Erm50 [ 25 ] and Erm51 [ 26 ] were added to them. To the authors’ knowledge, these are all Erm proteins reported at the time of submission of the paper.…”
Section: Resultsmentioning
confidence: 99%
“…The expression vector (pHJJ105) and E. coli strain ( E. coli HJJ105) overexpressing the wild-type ErmS was obtained in previous studies [ 25 , 34 ]. Site-directed mutagenesis was carried out by a sequential PCR method designated overlap extension PCR [ 47 ].…”
Section: Methodsmentioning
confidence: 99%